The Sacred Body: Asceticism in Religion, Literature, Art, and Culture. By David Jasper - Collins, Paul M. (The journal of theological studies, 2010)
InThe Sacred Body David Jasper offers the reader ten ‘meditations’ which are ‘experiments in different forms of writing’ (p. xi). These meditations, which are ‘conversations’ ‘with self and others’ and Scripture, also contain autobiographical material. Jasper himself suggests that while the book is in some sense ‘academic’ it is not written for ‘academic judgment’, but ‘for a form of response that is both simpler and much more difficult’ (p. xi). Of the ten meditations or chapters, four have appeared in earlier versions: chapters 3, 5, 7, and 9.